2011
DOI: 10.1186/1471-2458-11-228
|View full text |Cite
|
Sign up to set email alerts
|

Study of recent and future trends in place of death in Belgium using death certificate data: a shift from hospitals to care homes

Abstract: BackgroundSince most patients prefer out-of-hospital death, place of death can be considered an indicator of end-of-life care quality. The study of trends in place of death is necessary to examine causes of shifts, to evaluate efforts to alter place of death and develop future policies. This study aims to examine past trends and future projections of place of death.MethodsAnalysis of death certificates (decedents aged ≥ 1 year) in Belgium (Flanders and Brussels Capital region) 1998-2007. Trends in place of dea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
98
1
10

Year Published

2013
2013
2021
2021

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 114 publications
(115 citation statements)
references
References 30 publications
(40 reference statements)
6
98
1
10
Order By: Relevance
“…In the present study, only the presence of an adjacent affiliated hospital was consistent with the findings of previous studies (15,16,25,26). These studies showed that facility determinants of dying in nursing homes were the existence of a basic policy for EOL care, a physician based in a home care supporting clinic, location in a rural region, being adjacent to an affiliated hospital, being government-owned, location in regions with more nursing home beds, and location in regions with fewer hospital beds.…”
Section: Comparison With Other Studiessupporting
confidence: 82%
“…In the present study, only the presence of an adjacent affiliated hospital was consistent with the findings of previous studies (15,16,25,26). These studies showed that facility determinants of dying in nursing homes were the existence of a basic policy for EOL care, a physician based in a home care supporting clinic, location in a rural region, being adjacent to an affiliated hospital, being government-owned, location in regions with more nursing home beds, and location in regions with fewer hospital beds.…”
Section: Comparison With Other Studiessupporting
confidence: 82%
“…1,34 Nursing home deaths are likely to increase with population aging and with more people reaching very old ages. 34 Despite the need for qualitative and other research to establish why widowhood is a major place predictor and why most people chose the home over other places for their final days, the widespread home preference indicates public health interventions are needed to promote good home deaths.…”
Section: Discussionmentioning
confidence: 99%
“…1 Not only does the place of death or end-of-life (EOL) care impact the quality of death and dying, 2 but there are many direct and indirect costs and other considerations associated with the place of death and dying. 3 Although much has been made of the high cost of dying in hospitals and nursing homes, 4 home-based dying often involves significant out-of-pocket costs in addition to difficult tasks and responsibilities for family caregivers.…”
Section: Introductionmentioning
confidence: 99%
“…In some countries such as Japan and Belgium, a large share of deaths still occur in hospitals, while in the USA and Canada, death at home or in nursing homes is tending to replace death in hospital [3–7]. …”
Section: Introductionmentioning
confidence: 99%